2004
DOI: 10.1002/pola.11023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of semifluorinated block copolymers by atom transfer radical polymerization

Abstract: Two sets of styrene‐based semifluorinated block copolymers, one with a perfluoroether pendant group and another with a perfluoroalkyl group, were synthesized by atom transfer radical polymerization. Microphase separation of the block copolymers was established by small‐angle X‐ray scattering and differential scanning calorimetry (DSC). DSC measurements also showed that the perfluoroether‐based polymer had a low glass‐transition temperature (−44 °C). Contact‐angle measurements indicated that the semifluorinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Fluorinated (meth)acrylic monomers can be combined with a range of other monomers and have previously been copolymerized with monomers of similar character such as methyl methacrylate, butyl methacrylate, and styrene 42–44. For example, Zhang et al prepared a series of semifluorinated fluorocarbon/hydrocarbon diblock and triblock copolymers by ATRP with the macroinitiators obtained from bulk ATRP of styrene, butyl acrylate, and methyl acrylate 42.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorinated (meth)acrylic monomers can be combined with a range of other monomers and have previously been copolymerized with monomers of similar character such as methyl methacrylate, butyl methacrylate, and styrene 42–44. For example, Zhang et al prepared a series of semifluorinated fluorocarbon/hydrocarbon diblock and triblock copolymers by ATRP with the macroinitiators obtained from bulk ATRP of styrene, butyl acrylate, and methyl acrylate 42.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al prepared a series of semifluorinated fluorocarbon/hydrocarbon diblock and triblock copolymers by ATRP with the macroinitiators obtained from bulk ATRP of styrene, butyl acrylate, and methyl acrylate 42. Radhakrishnan et al reported the synthesis of a related PS block copolymer and a novel semifluorinated block copolymer with a perfluoroether pendant group by ATRP 43. Martinelli et al synthesized a new amphiphilic block copolymers consisting of two PS carrying an amphiphilic polyoxyethylene‐ b ‐polytetrafluoroethylene chain side‐group by ATRP 44.…”
Section: Introductionmentioning
confidence: 99%
“…65,66 These amphiphilic fluorous-ionic diblock copolymers were found to display varying degrees of nanophase separation dependent upon the ion content (IEC) of the styrene block. For 0.9-1.2 mmol/g IEC membranes, distinct perforated lamellae were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, controlled-radical polymerization, such as atom-transfer radical polymerization (ATRP), nitroxide-mediated radical polymerization (NMP), and reversible additionfragmentation chain transfer (RAFT) polymerization, has been widely developed and applied to perfluoroalkylated block copolymer synthesis, as shown in Figure 23.1 (Zhang et al, 1999;Lim et al, 2002;Hussain et al, 2002;Li et al, 2002a;Andruzzi et al, 2002;Gopalan et al, 2002;Radhakrishnan et al, 2004;Hikita et al, 2004;Shemper and Mathias, 2004;Jankova and Hvilsted, 2005;Galli et al, 2005). Styrene and (meth)acrylate monomers containing perfluoroalkyl groups are used as second monomers in sequential polymerization.…”
Section: Living/controlled-radical Polymerizationmentioning
confidence: 99%